Phenome-wide association study (PheWAS) in EMR-linked pediatric cohorts - Namjou, Bahram; Marsolo, Keith; Carroll, Robert; Denny, Joshua; Ritchie, Marylyn D.; setia, shefali; Lingren, Todd; Porollo, Aleksey; cobb, Beth; Perry, Cassandra; Kottyan, Leah C.; Holm, Ingrid A.; et al. (Frontiers in Genetics, 2014)
Objective: We report the first pediatric specific Phenome-Wide Association Study (PheWAS) using electronic medical records (EMRs). Given the early success of PheWAS in adult populations, we investigated the feasibility of this approach in pediatric cohorts. Method: Data on 5049 samples of European ancestry were obtained from the Electronic Medical Records (EMRs) of two large academic centers in five different genotyped cohorts. After standard quality controls, removing missing data and outliers based on principal components (PC) analyses, 4268 samples were used for the PheWAS study. We scanned for associations between 2476 single-nucleotide polymorphisms (SNP) with available genotyping data from previously published GWAS studies and 539 EMR-derived phenotypes. The false discovery rate was calculated and, for any new PheWAS findings, a permutation approach was implemented. Results: This PheWAS replicated a variety of common variants (MAF>10%) with prior GWAS associations in our pediatric cohorts including Juvenile Rheumatoid Arthritis (JIA), Asthma, Autism and Pervasive Developmental Disorder (PDD) and Type 1 Diabetes with a false discovery rate < 0.05 and power of study above 80%. In addition, several new PheWAS findings included a cluster of association near the NDFIP1 gene for mental retardation (best SNP rs10057309, p=4.33x10-7, OR=1.70, 95%CI=1.38-2.09), association at vicinity of (PLCL1, PRIP-1) gene for developmental delays and speech disorder (best SNP rs1595825, p=1.13x10-8, OR=0.65(0.57-0.76)), a cluster of SNP associations in the IL5-IL13 region, previously implicated in Asthma, Allergy, and Eosinophilia, with Eosinophilic Esophagitis (EE) (best SNP rs12653750, p=3.03x10-9, OR=1.73 95%CI=(1.44-2.07)) and association of variants in GCKR and JAZF1, responsible for metabolic disease and diabetes in adults with allergic rhinitis in our pediatric cohorts (best SNP rs780093, p=2.18x10-5, OR=1.39, 95%CI=(1.19-1.61)). Conclusion: By using the PheWAS approach and